Weighting Methods and their Effects on Multi-Criteria Decision Making Model Outcomes in Water Resources Management - Zardari, Noorul Hassan; Ahmed, Kamal; Shirazi, Sharif Moniruzzaman; Yusop, Zulkifli Bin (SpringerBriefs in Water Science and Technology,, 2015)
This book provides a systematic way of how to make better decisions in water resources management. The applications of three weighting methods namely rating, ranking, and ratio are discussed in this book. Additionally, data mining on keywords is presented using three popular scholarly databases: Science Direct, Scopus, and SciVerse. Four abbreviated keywords (MCDM, MCDA, MCA, MADM) representing multi-criteria decision-making were used and these three databases were searched for different popular weighting methods for a period of 13 years (2000-2012). The book provides also a review of weighting methods applied in various multi-criteria decision-making (MCDM) methods and also presents survey results on priority ranking of watershed management criteria undertaken by 30 undergraduate and postgraduate students from the Faculty of Civil Engineering, Universiti Teknologi Malaysia.